(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
Introduction: Organophosphorus poisoning is associated with high rate of mortality if not diagnosed and treated in time. Therefore aim of present study is to evaluate the significance of cholinesterase activity in assessing severity and to predict the outcome of Organophosphorus poisoning. Material and Methods: Present study was conducted in the department of Forensic Medicine, S.N. Medical College & Hospital, Agra during the period of 18 months (February 2011 to July 2012). Total 160 patients were enrolled after applying inclusion and exclusion criteria. Peradeniya Organophosphorus Poisoning Scale was applied to all study subjects. Result and Observation: Majority of patients were married (70%) and male (64%). About 42% of cases belong to the age group 21-30 years. About 1/3rd of the cases had low socioeconomic status and about 1/3rd cases were farmers by occupation. On applying Peradeniya Organophosphorus Poisoning (POP) Scale, about one third of patients had tachypnoea, followed by impaired consciousness (29%). Serum/ plasma cholinesterase level showed higher mortality in patients having suppressed cholinesterase activity (< 4000 IU/L). Conclusion: Organophosphorus poisoning diagnosed at early stages of poisoning determining pseudocholinesterase activity form a reliable diagnostic test for management and can serve as lives saving tool.